Zinc: an endogenous and exogenous regulator of platelet function during hemostasis and thrombosis. (3rd October 2021) - Ahmed, Niaz Shahed; Lopes-Pires, MariaElisa; Pugh, Nicholas
Abstract: Zinc (Zn 2+ ) is an essential micronutrient and the second most abundant trace metal in the human body. The important role that Zn 2+ plays in hemostasis is exemplified by platelet-related bleeding phenotypes coinciding with dietary Zn 2+ deficiency. These phenotypes are rectified upon Zn 2+ supplementation. Labile (unbound) Zn 2+ is present in the plasma at micromolar levels, but is also detected in atherosclerotic plaques, and released from platelet α granules. Therefore, it is likely that localized Zn 2+ concentrations are higher at sites of thrombosis and hemostasis. Exogenous Zn 2+ is a regulator of the hemostatic responses, with roles during coagulation and platelet activation. Extracellular Zn 2+ gains access to the platelet cytosol and induces full platelet activation at high concentrations, and potentiates platelets to activation by conventional agonists at lower concentrations. Zn 2+ -induced platelet activation is dependent on PKC and integrin αIIb β3, and is associated with tyrosine phosphorylation of platelet proteins. Agonist evoked platelet activation results in intracellular Zn 2+ ([Zn 2+ ]i ) fluctuations that are sensitive to the platelet redox state. Increases in [Zn 2+ ]i correlate with activation responses, including shape change, granule release, αIIb β3 activation and phosphatidyl-serine exposure, consistent with a role as a second messenger. This review provides insight into the numerous demonstrated and potential roles for Zn 2+ in platelet function during thrombosis and hemostasis, highlighting its increasing acceptance as an intracellular and extracellular platelet regulatory agent.